2021
DOI: 10.1093/jee/toab229
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Two Novel Host-Derived Beauveria bassiana (Hypocreales: Cordycipitaceae) Isolates Against the Citrus Pest, Diaphorina citri (Hemiptera: Liviidae)

Abstract: The Asian citrus psyllid (ACP), Diaphorina citri Kuwayama (Hemiptera: Liviidae), vectors ‘Candidatus Liberibacter spp.’, the causative agent of Citrus Greening Disease (CGD) or Huanglongbing (HLB). Managing populations of psyllids in the Lower Rio Grande Valley (LRGV), TX, United States is imperative given a continuous increase in HLB-positive trees. A component of integrated pest management (IPM) program is the use of strains of entomopathogenic fungi for the biological control of D. citri. In an attempt to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Investigating the results found through bibliometric analysis and the data presented in each research, we found that some of them were developed through the isolation of fungi native to the region where the studies were carried out, obtained by collecting naturally infected psyllid cadavers in the field, subsequently performing the morphological and genetic characterization, as well as the identification of the isolated fungi. Among eight researches initiated in this way, six were carried out in China, with the other two coming from the United States and Mexico (Lu et al, 2015;Awan et al, 2021a;Awan et al, 2021b;Qasim et al, 2021;Cisneros et al, 2022;Luo et al, 2022;Yan et al, 2022). This procedure reinforces the importance of considering the specificity of each isolate, in addition to the species of entomopathogenic fungus recommended for control and the geographic region from which the isolate originates, depending on the environmental conditions favorable for the fungus development.…”
Section: Rosasmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating the results found through bibliometric analysis and the data presented in each research, we found that some of them were developed through the isolation of fungi native to the region where the studies were carried out, obtained by collecting naturally infected psyllid cadavers in the field, subsequently performing the morphological and genetic characterization, as well as the identification of the isolated fungi. Among eight researches initiated in this way, six were carried out in China, with the other two coming from the United States and Mexico (Lu et al, 2015;Awan et al, 2021a;Awan et al, 2021b;Qasim et al, 2021;Cisneros et al, 2022;Luo et al, 2022;Yan et al, 2022). This procedure reinforces the importance of considering the specificity of each isolate, in addition to the species of entomopathogenic fungus recommended for control and the geographic region from which the isolate originates, depending on the environmental conditions favorable for the fungus development.…”
Section: Rosasmentioning
confidence: 99%
“…This may have been due to the larger size of the experimental units used in the field, environmental conditions and higher temperatures, humidity variation, wind, and rain. In the study byGandarilla-Pacheco et al (2013), nymphs of D. citri sprayed with a suspension of C. fumosorosea showed higher mortality (84.2%), while nymphs sprayed with B. bassiana showed greater development of mycosis.More recently, a study performed byCisneros et al (2022) under laboratory conditions identified and evaluated two isolates of B. bassiana through two application forms: direct insect spraying and exposure of psyllid adults on sprayed foliage.…”
mentioning
confidence: 99%